Reduction of Torque Ripple for Interior Permanent Magnet Motor with Fractional-Slot Concentrated-Windings. (July 2020) - Le, Wang; Dejun, Yin
Abstract: Fractional slot concentrated winding motors have advantages of compact structure, high efficiency and high power density, and are widely used in various fields. Due to the large torque fluctuation caused by improper design, it is necessary to pay attention to the torque ripple of the motor. This paper analyses the torque ripple of an 18-slot 12-pole motor, and provides a new method to reduce cogging torque and torque ripple torque through optimizing the harmonic magnetic field generated by permanent magnets. Finally, the validity of the method is verified by the FEM method.